Pelatihan Perhitungan Harga Pokok Produksi Berbasis Microsoft Excel - Windasari, Wahyuni; Zakiyah, Tuti; Kabul Trifiyanto (LP3M Universitas Putra Bangsa, 2022)
This community service activity was motivated by the Kebumen Regency Youth Care and Pioneering Development concern for MSME. One of the basic problems that are often faced by MSME is determining the cost of production. Currently, the selling price set by MSME is an estimated selling price or even follows competitors' prices. The lack of knowledge related to accounting and financial management is one of the factors driving MSME not to apply HPP calculations in determining the selling price of their products. This can cause MSME errors in compiling income statements. This community service activity aims to increase the knowledge of MSME regarding the determination of HPP based on financial management and accounting knowledge while at the same time increasing their soft skills in calculations using Microsoft Excel. The results of this service activity, MSME can classify fixed cost components and variable costs, determine production costs and overhead costs, and calculate HPP either manually or using Ms. Excel based accounting calculations.